2021
DOI: 10.3758/s13421-021-01209-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in mental imagery in different modalities and levels of intentionality

Abstract: Mental imagery is a highly common component of everyday cognitive functioning. While substantial progress is being made in clarifying this fundamental human function, much is still unclear or unknown. A more comprehensive account of mental imagery aspects would be gained by examining individual differences in age, sex, and background experience in an activity and their association with imagery in different modalities and intentionality levels. The current online study combined multiple imagery self-report meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 128 publications
2
24
0
Order By: Relevance
“…For instance, greater imagery strength was positively associated with greater visual working memory ( Keogh and Pearson, 2014 ). The relationship between reported imagery vividness and individual differences is found to be related to many aspects, including background experience in a related activity such as sports ( Di Corrado et al, 2014 ), music ( Aleman et al, 2000 ), and video games ( Floridou et al, 2021 ). Especially for less frequent words, the individual differences between vocabulary and world knowledge word processing speed might be another underlying factor for the imageability ratings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, greater imagery strength was positively associated with greater visual working memory ( Keogh and Pearson, 2014 ). The relationship between reported imagery vividness and individual differences is found to be related to many aspects, including background experience in a related activity such as sports ( Di Corrado et al, 2014 ), music ( Aleman et al, 2000 ), and video games ( Floridou et al, 2021 ). Especially for less frequent words, the individual differences between vocabulary and world knowledge word processing speed might be another underlying factor for the imageability ratings.…”
Section: Discussionmentioning
confidence: 99%
“…One way in which we can discuss imagery use is through intentionality and whether mental imagery is experienced voluntarily, meaning an individual can willingly call up images within their mind, or involuntarily, such as whilst experiencing intrusive thoughts (Floridou, Peerdeman & Schaefer, 2022).…”
Section: Mental Imagery Processesmentioning
confidence: 99%
“…It is widely assumed that designers rely heavily on mental imagery, in particular on visual mental imagery, and that visual mental imagery is an essential part of design cognition (Hart & Hay, 2022). However, research shows that there are considerable variations in the experience of mental imagery, from different sense imagery (Floridou, Peerdeman & Schaefer, 2022) to differing levels of clarity between individuals (Gallagher, 2019;Zeman, 2021). There are even reports of distinguished animation artists (Gallagher, 2019) and visual artists (Zeman, 2021) reporting that they experience no visual imagery, and while product design engineering is a very different type of design to art and animation, there are similarities in the assumptions made regarding creative professions and visual mental imagery (Hart & Hay, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is congruent with the previous research which showed that participants switched backwards and forwards between visual imagery and motor imagery rather than use them concurrently (Collins et al, 1998;Olsson et al, 2008), since limited information are allowed to be displayed in working memory (Pylyshyn, 2003). However, studies provided evidence supporting that the experience of visual imagery and motor imagery can be concurrently (Cumming and Ste-Marie, 2001;Callow and Roberts, 2010;Floridou et al, 2022). Therefore, whether the individual differences in dance performance between amateur dancers and non-dancers is associated with the switching ability between visual imagery and motor imagery remain to be explored.…”
Section: The Individual Differences Between Amateur Dancers and Non-d...mentioning
confidence: 99%